PENGARUH UMUR PANEN TERHADAP KARAKTERISTIK TEPUNG JAGUNG PULUT PUTIH (Zea mays var. ceratina) - Sahilatua, Ferdinandus Otniel; Suter, I Ketut; Wiadnyani, A.A.I Sri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 4 (2019): Jurnal ITEPA, 2019)
The purpose of this research is to know how the age of harvest effecting the characteristic of white waxy corn flour, and to determine the exact age of harvest to be able to produees the best charasteristic of white waxy corn flour. The experiment was used complete randomized design which the ages of harvest were on day 65 th , day 69 th , day 73 rd , day 77 th , day 81 st , day 85 th , day 89 th an day 93 rd , and the experiment was repeated twice so there will be 16 samples. After that, the white waxy corn flour will be examined for their chemical contents, it covers the water content, ash content, protein content, fat content, crude fiber, starch content, amylose content, acid degree, the color and the sensory levels. The results show that age of harvest was significantly effecting the charasteristic of white waxy corn flour. Proper harvest age is on day 85th with the characteristic that consist of 7,75% of water, 2,64% of ash, 18,67% of protein, 11,61% of fat, 4,29% of crude fiber, 3,62% of amylose, 61,28% of starch, 1,09% of acid, yellowish white color score, rather liked hedonic color, typical of corn scoring aroma, rather liked hedonic aroma and liked overall acceptance. Keywords : white waxy corn, age of harvest, charasteristic of white waxy corn